Electrodermal synchrony of patient and therapist as a predictor of alliance and outcome in psychotherapy - Tschacher, Wolfgang; Ribeiro, Eugénia; Gonçalves, Alexandra; Sampaio, Adriana; Moreira, Pedro; Coutinho, Joana (Frontiers in Psychology, 2025)
Previous empirical psychotherapy studies have been analyzing patient-therapist physiological synchrony as an important marker of an adaptive interpersonal co-regulation process between patient and therapist, and therefore a process essential for developing the therapeutic alliance. Yet, research on synchrony of the electrodermal activity and its relationship with the therapeutic alliance is still scarce, with inconsistent findings. The present study aimed to analyze the association between electrodermal synchrony, a signature of coordinated sympathetic activation, and the quality of the therapeutic alliance throughout the therapeutic process. Twenty-one therapeutic dyads were recruited, consisting of 21 different patients with a diagnosis of major depressive disorder or social anxiety disorder, treated by six therapists. For each dyad, electrodermal activity was recorded during all 16 sessions of Cognitive-Behavioral Therapy. The Working Alliance Inventory and the Session Evaluation Questionnaire were administered at each session to monitor the quality of the alliance and the respective session. Symptomatic improvements were measured with outcome questionnaires. We found clear evidence for the presence of in-phase electrodermal synchrony of therapists and patients. Additional results were that patient-leading synchrony was significantly more pronounced than therapist-leading synchrony, and that this leading role of patients in their sympathetic interactions during sessions was positively linked with the quality of the therapeutic bond as rated by the therapist, and negatively linked with patients’ distress.